Project module for strengthening the profile of Pancasila students in the perspective of 21st-century learning design microsoft - Prihantini, Prihantini; Khoirunnisa, Qori (Univeritas Papua, 2023)
The objective of this study is to identify and evaluate the content of the module in terms of 21st-century learning design (21 CLD) dimensions. This study adopts a qualitative approach by applying the content analysis method of Krippendorff's model. The object of content analysis is the project module for strengthening the profile of Pancasila students with the theme of local wisdom for phase A of elementary school. The researcher is the primary tool employed in this study. The content analysis instrument uses a rubric that microsoft developed to determine the dimension level of each learning activity in the module. The data is collected using six phases to analyze the content, explicitly unitizing, sampling, recording, reducing, abductively inferring, and narrating. The project module for strengthening the profile of Pancasila students was identified as containing 5 of the six dimensions of microsoft's 21 CLD.